Effectiveness of Bacterial Culture Preservative Techniques in the Microbiology Laboratory - Trisiswanti; Arista, Anggi Maulia; Sugimin, Sugimin; Rizquita, Eza Alfian; Oxi, Rizki Yulia (Proceeding of International Joint Conference on UNESA, 2024)
Short-term or long-term preservation goals are adjusted to program objectives to be designed. Various kinds of studies or research are carried out in the Laboratory Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences, University State of Surabaya part great use isolate microbes as material the test. Bacterial culture storage space (refrigerator) is limited, so it is important for done study for find method which appropriate storage bacteria Escherichia coli and Staphylococcus aureus in glycerol medium. Isolate S. aureus and E. Coli bacteria which have been recultured and incubated on nutrient agar media (NA) moved on media Nutrients Broth which has containing Sterile Cryoprotectant Agent. Preservation of S. aureus and E. Coli bacterial isolates was carried out for 1- 3 weeks. Each was repeated 3 times with additions glycerol 30%, 40%, and 50%. Results test the can made-based in determine Cryoprotectant Agent best. growth research macroscopic bacteria S. aureus and E. Coli preserved on glycerol 30%, 40%, and 50% is best preserved using 30% Glycerol, while for growth microscopic S. aureus And E. Coli Which preservatif 30%, 40% and 50% glycerol, the best preservation is using 40% glycerol.